Pola Perilaku Masyarakat Lokal dalam Mengelolah Sumber Daya laut melalui Berkarang di Teluk Bakau Kepulauan Riau - Fadillah, Mohammad Rizky; Aidin Fitrah Bachtiar (RISOMA : Jurnal Riset Sosial Humaniora dan Pendidikan, 2026)
This research examines the behavior of local communities in Teluk Bakau, Bintan, in managing marine resources through the practice of nesting, which represents an important form of local wisdom that has been passed down through generations. The background of this research is the increasing challenges faced by Indonesia's coastal areas, including marine pollution, environmental degradation, and the impacts of climate change on coastal ecosystems. The aim of the study was to understand community behavior patterns in nesting activities and to analyze their impact on the sustainability of the marine ecosystem. The methods used included structured observations supported by purposive and random sampling techniques to obtain representative data. The results showed that the community conducts nesting activities during low tides; however, yields have decreased due to pollution and unstable market prices. In addition, community knowledge regarding the ecological benefits of seagrass ecosystems remains limited. The conclusions emphasize the importance of education programs and sustainable marine resource management to enhance environmental awareness and improve the welfare of local communities.